Dynamic prediction of metastases after radical prostatectomy for prostate cancer - Inman, Brant A.; Frank, Igor; Boorjian, Stephen A.; Akornor, Joseph W.; Karnes, R. Jeffrey; Leibovich, Bradley C.; Blute, Michael L.; Bergstralh, Eric J. (BJU international, 2011)
Study Type – Prognosis (retrospective cohort) Level of Evidence 2a What’s known on the subject? and What does the study add? One of two problems plagues virtually are existing post‐prostatectomy prediction tools: either (1) they predict PSA recurrences (which are of unclear importance) or (2) the predictions they make are anchored at the date of surgery and are not updated based on how patients evolve over the postoperative years. Our prediction tool is a significant improvement over existing prediction tools in that it predicts the development of metastases which is a very important clinical endpoint that indicates incurable prostate cancer. Additionally, our tool allows for updated predictions at any point following radical prostatectomy by considering commonly available postoperative information (postoperative serum PSA and use of adjuvant therapies) to modify its risk predictions. The net result is a dynamic tool that renders clinically relevant predictions that change as the patient’s clinical status changes throughout the postoperative course. OBJECTIVE • To develop a dynamic algorithm that predicts the risk of metastases from any time point after radical prostatectomy (RP). PATIENTS AND METHODS • The study cohort consisted of 5741 RP patients who were treated from 1990–99. • Patients were grouped into one of four clinical states at follow‐up: State1, prostate‐specific antigen (PSA) undetectable; State2, PSA 0.15–0.39 ng/mL; State3, PSA ≥0.4 ng/mL; and State4, previous androgen deprivation or radiation therapy. • Follow‐up epochs (alive and at risk of systemic progression) at 0, 2, 4 and 6 years post‐RP, cumulative incidence curves and multistate Cox models were used to assess the risk of metastases over the ensuing 5‐year interval. • Gleason score, seminal vesicle and surgical margin involvement, and PSA variables were evaluated as predictors. RESULTS • Median follow‐up was 11.7 years, with 4411, 4256 and 3983 patients followed with PSA at 2, 4 and 6 years, respectively. • In total, 287 metastatic events occurred and the 5‐year risk of metastasis was 0.4%, 2.1%, 8.7% and 12.6% for men in States 1, 2, 3 and 4, respectively. • Independent predictors of metastasis by group included seminal vesicle involvement (all groups), Gleason score (groups 1, 3 and 4), current PSA (groups 3 and 4) and maximum past PSA (group 4). CONCLUSIONS • We present a web‐based prognostic tool for patients undergoing RP that is valid at many time points after surgery. • Our tool predicts the development of metastases.